Design and Hardware Integration of Elastic Actuators for HMI - Pott, Peter Paul; Beckerle, Philipp; Stewart, Kent W. (Novel Bioinspired Actuator Designs for Robotics, 2021)
In this chapter, the basic mechanical setup is described and its potential for human-machine interaction and how it can be leveraged by design and hardware integration is discussed.
CRIS-Team Scopus Importer:2021-09-17